Manajemen Laboratorium Fisika di Universitas PGRI Silampari - Athiyyah Nur Rahmah; Bunga Zahaa Aureli; Adi Frengki Wibowo; Nirwana Atiqah Al-Fajri; Sulistiyono (Global Action and Education for Society, 2026)
Physics laboratories play a strategic role in supporting experiment-based learning in higher education, but their management often faces various obstacles that affect the effectiveness of practical work. This study aims to describe and analyze the management of physics laboratories at PGRI Silampari University in supporting the physics learning process. The research uses a descriptive approach with qualitative methods. Data collection techniques include observation, interviews, and documentation involving the laboratory head, laboratory assistants, lecturers in charge of practicums, and students. The results of the study show that physics laboratory management has generally been running quite well and functions as the main supporting facility for practicum activities. Laboratory planning and organization have been carried out in accordance with academic needs, but have not been supported by systematic long-term development planning. The management of facilities and infrastructure as well as human resources still faces limitations, especially in terms of the number of practical tools, inventory systems, and the number of laboratory assistants. In addition, the implementation of occupational safety and health has not been fully supported by continuous socialization to students. Thus, it is necessary to improve the management of the physics laboratory through strategic planning, human resource development, modernization of the management system, and continuous evaluation in order to improve the quality of physics learning at PGRI Silampari University.